High mobility group box 2 of black rockfish Sebastes schlegelii: Gene cloning, immunoregulatory properties and antibacterial effect. Issue 84 (January 2019) - Wang, Guang-hua; Wang, Jing-jing; Yue, Bin; Du, Xue; Du, He-he; Zhang, Min; Hu, Yong-hua
Abstract: High-mobility group box 2 (HMGB2) is a non-histone chromosomal protein that involved diverse functions such as transcriptional regulation and innate immune responses in mammalian. In teleost, very limited studies on HMGB2 proteins have been documented. Black rockfish ( Sebastes schlegelii ) is an economic ﬁsh species and cultured worldwide. However, the study of black rockfish about immunology is very scarce. In the present study, a HMGB2 homologue gene ( SsHMGB2 ) was identified and characterized in black rockfish. The open reading frame of SsHMGB2 is 648 bp, and the deduced amino acid sequence of SsHMGB2 shares 74.4%–91.2% overall sequence identities with the HMGB2 proteins of several fish species. In silico analysis identified several conserved features, including two basic HMG boxes and an acidic C-terminal tail composed of 24 Asp/Glu residues. Expression of SsHMGB2 occurred in multiple tissues and was upregulated during pathogens infection. Recombinant SsHMGB2 (rSsHMGB2) exhibited apparent binding activities against DNA. In vivo studies showed that the expressions of multiple immune-related genes in head kidney were significantly enhanced when black rockfish were treated with rSsHMGB2. Furthermore, rSsHMGB2 reduced pathogen dissemination and replication in fish kidney and spleen. Taken together, these results suggest that SsHMGB2 possesses apparent immunoregulatory properties and played a role in fighting bacterial infection. Highlights: A HMGB2 homologue ( SsHMGB2 ) in black rockfish was identified and characterized. Expression of SsHMGB2 occurred in multiple tissues and was upregulated during pathogens infection. Recombinant SsHMGB2 exhibited apparent binding activities against DNA. Recombinant SsHMGB2 possesses apparent immunoregulatory property and is involved in fighting bacterial infection.